Elevated levels of autoantibodies against DNAJC2 in sera of patients with atherosclerotic diseases. Issue 8 (August 2020) - Yoshida, Yoichi; Zhang, Xiao-Meng; Wang, Hao; Machida, Toshio; Mine, Seiichiro; Kobayashi, Eiichi; Adachi, Akihiko; Matsutani, Tomoo; Kamitsukasa, Ikuo; Wada, Takeshi; Aotsuka, Akiyo; Iwase, Katsuro; et al.
Abstract: Background: Serum antibody markers have been increasingly identified not only for cancer and autoimmune diseases but also for atherosclerosis-related diseases such as acute ischemic stroke (AIS), acute myocardial infarction (AMI), diabetes mellitus (DM), and chronic kidney disease (CKD). Biomarkers for transient ischemic attack (TIA) and non-ST segment elevation acute coronary syndrome (NSTEACS) are potentially useful for detection of early phase of atherosclerotic changes against AIS and AMI, respectively. Methods: We utilized serological identification of antigens by recombinant cDNA expression cloning (SEREX) using a human aortic endothelial cell cDNA phage library and sera from patients with TIA or NSTEACS. Serum antibody levels were measured by amplified luminescent proximity homogeneous assay-linked immunosorbent assay (AlphaLISA) using purified recombinant antigens. Results: Screening of sera from patients with TIA identified DnaJ heat shock protein family (Hsp40) member C2 (DNAJC2) as a candidate antigen, which was also isolated by SEREX screening using sera of patients with NSTEACS. The validation cohort revealed significantly higher DNAJC2 antibody (DNAJC2-Ab) levels in the sera of patients with TIA or AIS than those in healthy donors (HDs). Multivariate logistic regression analysis indicated that the predictive odds ratios (OR) of DNAJC2-Ab levels for TIA and AIS were 2.54 (95% confidence interval [CI]: 1.36–4.74, p = 0.0034) and 2.14 (95% CI: 1.39–3.30, p = 0.0005), respectively. Serum DNAJC2-Ab levels were also higher in patients with AMI, DM, and CKD than those in HDs. Conclusion: Serum DNAJC2-Ab level may be useful for early detection of atherosclerotic lesions, which lead to AIS and AMI. Abstract : Cardiovascular system; Hematological system; Neurology; Neurosurgery; Clinical research; Diagnostics; Biomarkers; DNAJC2; Acute ischemic stroke; Acute myocardial infarction; Autoantibody biomarker; Atherosclerosis, Cardiology